Increased Production and Molecular Weight of Artificial Polyhydroxyalkanoate Poly(2-hydroxybutyrate) Above the Glass Transition Temperature Threshold - Matsumoto, Ken'ichiro; Kageyama, Yuki (Frontiers in Bioengineering and Biotechnology, 2019)
Poly(2-hydroxybutyrate) [P(2HB)] is an artificial polyhydroxyalkanoate (PHA) synthesized using engineered 2-hydroxyalkanoate-polymerizing PHA synthase. In the present study, the effect of temperature on P(2HB) synthesis was investigated. Recombinant Escherichia coli harboring PHA synthetic genes were cultivated with 2HB and 3-hydroxybutyrate (3HB) supplementation at varied temperatures ranging from 24 to 36°C for the synthesis of P(2HB) and natural PHA P(3HB), respectively. P(2HB) production and its molecular weight increased considerably at a threshold temperature of 32°C–34°C. The trend was not observed during the synthesis of P(3HB). Notably, the threshold temperature was close to the glass transition temperature (Tg) of P(2HB) (30°C), while the Tg of P(3HB) (4°C) was much lower than the cultivation temperature. The results suggest that thermal motion of the polymer chains influenced the production and molecular weight of the obtained polymer. According to the results, the production and molecular weight of PHA drastically changes at the threshold temperature, which is linked to the Tg of the polymer. The hypothesis should be applicable to PHAs in general, and potentially explains the inability to biosynthesize high-molecular-weight polylactate homopolymer with a Tg of 60°C.